Techno-economic analysis of cement-based composite mortars for energy-efficient buildings - Jeanne Leclerc; Abdul Wasy Zia (Green Technologies and Sustainability, 2025)
This article explores thermal insulating cement-based mortars in aspiration of increasing demand for sustainable materials to improve building energy efficiency. Cement mortars are widely used around the globe, and integrating lightweight and insulating aggregates such as sand replacements offers better energy efficiency and minimize energy losses in buildings. The techno-economic analysis in this work evaluates composite mortars by incorporating aerogel, expanded clay, and expanded polystyrene aggregates, in line with European standards EN998-1. Their performance is assessed as a function of percentage sand replacement, thermal conductivity, compressive strength, density, and cost. Integrating insulating aggregates reduces compressive strength and density, impacting mechanical resistance and structural weight. Therefore, this analysis identifies the optimal material composition by replacing sand with 67% aerogel and 100% expanded clay and expanded polystyrene to maintain a balance between thermal and mechanical performance. It is perceived that the aerogel exhibits the best insulation properties, but they are the most expensive candidate. The techno-economic analysis also examines the optimal thickness, revealing that expanded polystyrene can reduce energy consumption by up to 86% at the break-even point, though it requires an impractically thick layer of over 8 cm. The decision support system developed in this study recommends expanded polystyrene as the most cost-effective option for achieving 50% energy savings and CO2 reduction of up to 68%.